Prenatal compensatory renal growth in unilateral renal agenesis. (November 2016) - Perlman, Sharon; Lotan, Dani; Dekel, Benjamin; Kivilevitch, Zvi; Hazan, Yinon; Achiron, Reuven; Gilboa, Yinon
Abstract: Objective: To create nomograms of fetal renal compensatory growth in cases of unilateral renal agenesis (URA). Methods: A retrospective study of fetuses with isolated URA diagnosed prenatally, and confirmed postnatal was performed. Results: Seventy‐four fetuses with isolated solitary kidney were included in the study. A total of 134 measurements of the kidney's length were performed. Ninety five of them were studied longitudinally (2–6 measurements each). The raw values of the compensatory kidney demonstrated a significant correlation with gestational age (Pearson correlation coefficient 0.901, p  < 0.001). A quadratic/cubic regression curve, both, described best this relationship, −26.400 + 3.004*GA, −0.026*GA 2 ( r 2  = 0.819). The Z score between the mean predicted compensatory kidney's length, per week of gestation, and the mean predicted values of normal kidney length as previously published in the literature, progressively increased during pregnancy (cubic r 2  = 0.946 and 0.260). Conclusion: Cases of URA show a unique growth pattern of the single kidney from second trimester to term. Postnatal renal function is dependent on adequate intra‐uterine compensatory growth; the presented nomograms provide insight into renal prognosis and add paramount information to the multidisciplinary prenatal counseling of the future parents. © 2016 John Wiley & Sons, Ltd. Abstract : What's Already Known About This Topic? Low nephron endowment has been found to be associated with increased risk of developing hypertension and chronic renal failure as an adult. A correlation exists between prenatal renal measurements and number of nephrons. What Does This Study Adds? Cases of unilateral renal agenesis show a unique growth pattern of the solitary kidney independent of the normative data. The growth increment is steeper during the second trimester than in the third trimester. Our data suggest that definition of compensatory growth as measurements above the normal 95th percentile for gestational age should be replaced by nomograms specific for unilateral agenesis.